Community-Based Willingness to Pay for Urban Flood Mitigation Infrastructure: Sustainable Environmental Practices from Glintung, Indonesia - Muljaningsih, Sri; Ekawaty, Marlina; Anggraini, Ika Khusnia; Galuh , Ajeng Kartika (Economics Departement, Faculty of Business and Economics, Universitas Surabaya, 2025)
This study investigated residents' willingness to pay (WTP) for community-based flood mitigation infrastructure through a Malang, Indonesia, case study of the Glintung Go Green (G3) program. This study aimed to identify the key factors influencing WTP and assess the structural and cultural challenges in sustaining such community-based environmental programs. A mixed method approach was applied, combining focus group discussions (FGDs) with quantitative analysis using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that socio-economic factors and personal motivation significantly influenced WTP, with education levels and perceived direct benefits of the program being the most influential indicators. The average WTP value is IDR 37,273 per month, with a median of IDR 50,000, showing promising potential for participatory financing mechanisms. However, the FGD revealed critical barriers, including low ecological literacy, reliance on external funding, limited community leadership regeneration, and lack of documentation for replication. These findings underscore the importance of institutionalizing environmental values, building local capacity, and leveraging digital tools for program transparency and outreach. The study concludes that community-based environmental programs should integrate financial and institutional strategies to improve long-term sustainability and inclusivity. Future research is encouraged to explore broader psychosocial and institutional factors that influence community participation